Preparation, characterization and reduction of burst release of BSA from biodegradable PLGA microspheres - Rahman, Md. Mokhlesur; Ansary, Rezaul Haque; Mohamed, Farahidah; Awang, Mohamed; Yunus, Kamaruzzaman; Katas, Haliza (2014)
BSA loaded hydroxyl terminated-PLGA and acid-terminated-PLGA microspheres have been prepared by a conventional water-in-oil-in-water (w/o/w) and a modified water-in-oil-in-oil-in-water (w/o/o/w) emulsion solvent evaporation method. In modified w/o/o/w emulsion technique, 100 µl of BSA solution (30 mg/ml) in 1% aqueous PVA (w/v) was emulsified with 50 mg of carboxyl terminated-PLGA in ethyl acetate (EA). This water/oil emulsion was then emulsified with 50 mg of hydroxyl terminated-PLGA in dichloromethane (DCM). The obtained w/o/o emulsion was further emulsified with 10 ml of 1% PVA. The resulting w/o/o/w emulsion was transferred into 50 ml of 0.5% PVA (w/v) aqueous solution and stirred for three hours to evaporate EA/DCM solvent mixture by vacuum evaporation at room temperature. After that the microspheres were separated by centrifugation and washed 3 times with 60 ml distilled water and freeze dried overnight. In conventional w/o/w method, BSA loaded hydroxyl terminated-PLGA and acid terminated-PLGA microspheres have been prepared separately as well. The particle size distribution was expressed as the volume median diameter (D 50%). BSA encapsulation efficiency and in vitro release were determined by a micro BCA method. Microspheres prepared with w/o/w and w/o/o/w emulsion technique exhibited high encapsulation efficiency except formulation F3. High initial burst release of BSA was observed in all formulations prepared by w/o/w emulsion technique. A significant reduction of initial burst release of BSA (Table 2) was observed when microspheres were prepared by modified w/o/o/w emulsion method. The optimized formulation (F4) of BSA loaded microspheres was nonporous, smooth-surfaced, and spherical shape (Fig. 2) under field-emission scanning electron microscope (FE-SEM) with a mean particle size of 3.95 µm and encapsulation efficiency of 98.46%. In contrast, microspheres prepared with w/o/w double emulsion technique were porous (Fig. 1) which might be a reason of high initial burst release of BSA. It can be concluded that microspheres prepared with hydroxyl terminated-PLGA and carboxyl terminated-PLGA by modified w/o/o/w method can be proposed as a potential delivery system of therapeutic proteins.